Peran Literasi Akuntansi sebagai Moderasi Hubungan Penggunaan Aplikasi Keuangan dan Literasi Keuangan Gen Z di Provinsi Sumatera Utara - Hutabarat, Metyria Imelda; Widiyastuti, Tetty (Jurnal EMT KITA, 2026)
The development of digital technology has encouraged Gen Z to increasingly actively use financial applications in managing their personal finances. However, the high use of financial applications doesn’t necessarily mean adequate financial literacy. The reserach aims to demonstrate the role of accounting literacy as moderator in the relationship between the use of financial applications and financial literacy among Gen Z in North Sumatra Province. The research method used quantitative approach. Data collection techniques with questionnaires distributed to Gen Z respondents. The data were analyzed using moderated regression. The research sample consisted of 100 respondents. The results of reserach prove that the use of financial applications has positive and significant effect on financial literacy. The Adjusted R Square analysis value was obtained at 65%. Interestingly, accounting literacy has been shown to act as moderating variable that strengthens the relationship between the use of financial applications and financial literacy. The findings indicate that good understanding of accounting can increase the effectiveness of the use of financial applications in shaping better financial behavior and understanding in Gen Z. The implications of the findings can be the basis for developing technology-based financial literacy curriculum for the younger generation.